Envolvimento dos trabalhadores na gestão da produção e da qualidade na indústria de autopeças - Souza, Lílian Carneiro (Universidade Federal de São Carlos, 2013)
The purpose of this thesis is to verify if there is the involvement of workers in the use of different methods of operations management and how this process occurs, as recommended by handbooks, which recommend this involvement as necessary to the success of the methods. It was considered the auto parts companies as appropriate to investigate this topic, as they are forced to adopt many of the methods investigated. We chose the survey procedure using the database of member companies of Sindipeças, an association of auto parts producers, in 2010. In total, 388 companies were contacted and received the questionnaire. Of these, 95 returned the questionnaire answered. The main results observed were that methods of operations management listed in the questionnaire were adopted by companies surveyed and, in most cases, there was involvement of workers. It was also observed that the cases of adoption of methods without the involvement of workers were more discontinued.
Involvement of workers in production management and quality in auto parts industry
Keywords: Engenharia de produção; Indústria de autopeças; Organização do trabalho; Survey; Envolvimento do trabalhador; Métodos de gestão; Worker involvement; Management methods; Auto parts; ENGENHARIAS::ENGENHARIA DE PRODUCAO